Innovation in Malmö after the Öresund Bridge. (7th June 2021) - Ejermo, Olof; Hussinger, Katrin; Kalash, Basheer; Schubert, Torben
Abstract: We analyze the effect of the Öresund Bridge, a combined railway and motorway bridge between Swedish Malmö and the Danish capital Copenhagen, on inventive activity in the region of Malmö. Applying difference‐in‐difference estimation on individual‐level data, our findings suggest that the Öresund Bridge led to a significant increase in the number of patents per individual in the Malmö region as compared with the two other major regions in Sweden, Gothenburg, and Stockholm. We show that a key mechanism is the attraction of highly qualified workers to the Malmö region following the construction of the bridge.